Dommusikarchiv Salzburg (A-Sd). Thematischer Katalog der musikalischen Quellen, Reihe A. (Hollitzer Wissenschaftsverlag, 2018)
Wolfgang Amadé Mozart's church music was largely composed for the liturgy in the Salzburg Cathedral, the music holdings of which have been preserved as a closed collection. As a parish and metropolitan church, the cathedral was an important representative area of a clerical court and a center of church music with a national reputation. The catalog presented here from the Salzburg Cathedral Music Archive between the late 17th and mid-19th centuries opens up central sources for the work of such important composers as Heinrich Ignaz Franz Biber, Johann Ernst Eberlin, Leopold and Wolfgang Amadé Mozart, Michael Haydn and Luigi Gatti in their context of origin .